Making volunteering economically valuable: the relationship between valuation devices and volunteering. (24th November 2017) - Larsson, Ola Segnestam; Andersen, Rebecka
Abstract : This article contributes to previous research on determining the economic value of volunteering by analysing the relationship between the valuation devices being proposed and volunteering and its properties. Is the relationship best characterised as direct, mediated or imposed? The empirical material for the article consists of volunteering economic valuation devices, as presented in previous research, which are analysed with a framework derived from the theoretical field of valuation. In addition to introducing the analytical framework and its application to the field of volunteering, the article discusses the absence of direct relationships while underscoring the dominance of the mediated relationship. It also argues that the imposed relationship highlights a hitherto less-discussed analytical dimension in the research debate on valuing volunteering. In conclusion, the relevance of the findings are discussed and ideas for a future research agenda presented.